PROJECT-BASED WORKSHEETS USING A LESSON STUDY SYSTEM - Elisa Mayang Sari; Ratu Ilma Indra Putri (Jurnal Infinity, 2021)
Often students are only given practical problems in the form of algorithms without inviting them to think at a high level and almost never given daily problems in the form of projects. From this it can be seen that there are still teachers who have not carried out directives from the government that is to assess competencies made in the assessments that require students to demonstrate certain competencies using projects. This study aims to produce worksheets in the form of school cooperation projects on the value of direct proportion and social arithmetic, and analyze students' answers in solving these problems and the implementation of learning is carried out using a lesson study for learning community (LSLC) system. This research uses a design research method which is a form of qualitative approach. The stages in the design research type of development studies. The subjects of this study were seventh grade students of SMP Palembang. From this study, student worksheets were generated about direct proportion and social arithmetic consisting of four activities including determining the price list of goods purchased, determining the price of capital goods, reporting prices of goods and selling prices, and determining conditions of sale. Based on the results of the analysis of students' answers to worksheets, some students can perform procedures of direct proportion and determine conditions of sale (profit, loss, or break even) so that this worksheet has been deemed valid and practical to use.